2012
DOI: 10.1007/s00421-012-2322-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microcirculation of the trapezius muscle during a prolonged computer task

Abstract: The aim of this study is to investigate if there is a change in oxygen saturation and blood flow in the different parts of the trapezius muscle in office workers with and without trapezius myalgia during a standardized computer task. Twenty right-handed office workers participated; ten were recruited based on pain in the trapezius and ten as matching controls. Subjects performed a combination of typing and mousing tasks for 60 min at a standardized workstation. Muscle tissue oxygenation and blood flow data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Nevertheless, several reasons may explain the association between time spent in screen based activities and pain intensity: i) the flexed and end of range postures that students tend to use during screen based activities [33, 34] may place excessive strain and/or stretch on sensitive structures; the long periods of time spent in static positions may further contribute to increase strain while also decreasing the appropriate oxygenation and removal of metabolites and algic substances from tissues, increasing nociceptive activity. There is some evidence in support of the proposed hypothesis: a prospective study on the association between posture during desk top computer use and pain found that increased head flexion predicted pain of higher intensity even when adjusted for psychosocial factors [35]; 1 h of combined workstation tasks resulted in decreased oxygen saturation and blood flow in all three parts of the trapezius muscle and 90 min of computer based work significantly increase pain intensity [36]. Nevertheless, these arguments do not seem to apply to low back pain as more time using mobile phones was associated with lower pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several reasons may explain the association between time spent in screen based activities and pain intensity: i) the flexed and end of range postures that students tend to use during screen based activities [33, 34] may place excessive strain and/or stretch on sensitive structures; the long periods of time spent in static positions may further contribute to increase strain while also decreasing the appropriate oxygenation and removal of metabolites and algic substances from tissues, increasing nociceptive activity. There is some evidence in support of the proposed hypothesis: a prospective study on the association between posture during desk top computer use and pain found that increased head flexion predicted pain of higher intensity even when adjusted for psychosocial factors [35]; 1 h of combined workstation tasks resulted in decreased oxygen saturation and blood flow in all three parts of the trapezius muscle and 90 min of computer based work significantly increase pain intensity [36]. Nevertheless, these arguments do not seem to apply to low back pain as more time using mobile phones was associated with lower pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Different studies have reported changes in microcirculation during static low-level muscle contractions. Cagnie et al 7 and Flodgren et al 8 demonstrated a significant decrease in oxygen saturation of the trapezius muscle over time during a 1-hour typing task and 30-minute repetitive work, respectively. This decrease is likely to coincide with an increase in lactate, which is interpreted as a normal response to increased physical demands.…”
mentioning
confidence: 97%
“…This technique has been widely used in the evaluation of microcirculation in Achilles tendon problems [21][22][23] but has been shown to be also very applicable for the trapezius muscle. 7 The aim of this study is to investigate the effect of dry needling on blood flow and oxygen saturation of the trapezius muscle in healthy participants. We hypothesize that dry needling is able to immediately increase oxygen saturation and blood flow in the region where dry needling is performed, whereas no changes at the nonneedled sites are expected.…”
mentioning
confidence: 99%
“…Cagnie’s study with non-invasive technique showed that 1 hour of combined workstation tasks resulted in decreased oxygen saturation and blood flow in all three parts of the trapezius muscle[31]. During 1 hour typing work, case group with pain symptom showed lower blood flux on average.…”
Section: Discussionmentioning
confidence: 99%